Trace : the new Scarpetta novel - Cornwell, Patricia Daniels, 1953- (Time Warner, 2005)
Five years after being sacked as Chief Medical Examiner, Dr Kay Scarpetta returns to Richmond, Virginia ,as Consultant Pathologist in the mysterious death of a teenage girl.Gilly Paulsson's death has stumped the best in the business.There is no obvious cause ; nothing suspicious except for the fact that Gilly shouldn't be dead. Then Scarpetta uncovers trace evidence : Gilly Paulsson was murdered. But why? Scarpetta's niece, Lucy Farinelli , doesn't want her aunt to get involved and she also has troubles of her own. One of her operatives has been attacked in her home . And whoever attacked her has left clear evidence of his presence. It's as if he deliberately left traces... For Scarpetta, what began as a forensic puzzle expands into a larger , far more alarming picture. But still the vital pieces are missing. Who is the person tightenig a web arounf her and her loved ones? There's still mystery behind his methods -but not his murderous motives. "Revenge" is stamped all over this one..